Improving neuron-to-electrode surface attachment via alkanethiol self-assembly an alternating current impedance study - Slaughter, Gymama E (Langmuir : the ACS journal of surfaces and colloids, 2004)
In this work, the omega-amine alkanethiols, cysteamine (CA) and 11-amino-1-undecanethiol (11-AUT), were chemisorbed as self-assembled monolayers (SAMs) onto 250-microm gold microelectrodes that were microlithographically fabricated within eight-well cell culture plates and investigated as a means to improve neuron-to-electrode surface attachment (NESA). Dynamic contact angle (DCA) measurements showed similar advancing, theta(a) (69 degrees and 65 degrees ), but contrasting receding contact angles, theta(r) (9 and 30 degrees ) for CA- and 11-AUT-SAMs, respectively. The corresponding hysteresis (Deltatheta(ar) = 60 and 35 degrees, respectively) indicates the CA-SAM displays greater amphiphilic character than the 11-AUT-SAM. A portion of the greater Deltatheta(ar) for CA-SAMs may arise from surface heterogeneity, as compared to sputter-deposited gold and 11-AUT-SAMs. Tapping mode atomic force microscopy (AFM) confirmed a 6% increase (CA-SAM) and a 22% decrease (11-AUT-SAM) in surface roughness when compared to clean but unmodified, sputter-deposited gold. The extracellular matrix cell adhesion proteins, collagen, fibronectin, and laminin, were covalently coupled to the aminoalkanethiol-decorated gold electrodes via acid-amine heterobifunctional cross-linking. Using fluorescein isothiocyanate-tagged laminin, confocal fluorescence microscopy of both CA- and 11-AUT-SAM-modified and unmodified gold microelectrodes confirmed coupling of the protein to the electrode and was readily distinguishable from nonspecifically adsorbed protein. DCA measurements of laminin physisorbed directly onto gold or covalently immobilized via CA- or 11-AUT-SAM had similar advancing (ca. 63-65 degrees ) and receding (ca. 7-9 degrees ) contact angles. Tapping mode AFM of these protein-bearing surfaces likewise showed dimerized protein aggregates of similar surface roughness. PC-12 cells cultured to confluence on both unmodified and SAM-modified, protein-derivatized gold microelectrodes were examined by alternating current impedance (50 mV p-t-p at 4 kHz). CA- and 11-AUT-SAM-modified surfaces when serving as a foundation or covalently immobilized adhesion proteins produced highly stable and reproducible temporal impedance responses. On the basis of the magnitude and the reproducibility of the impedance responses, the CA-SAM-modified surfaces were identified as being best suited for optimal neuron-to-electrode contact with laminin. Laminin performed best when compared to collagen and fibronectin. Covalent immobilization of the adhesion-promoting proteins results in enhanced NESA by tightly anchoring cells to the electrode